Influencer Authenticity: Unraveling The Impact On Modern Marketing - Agnes Dini Mardani; Evrina Evrina; Bella Hartati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research investigates the dynamics of influencer authenticity and marketing effectiveness on consumer engagement and trust within PT. Unilever Indonesia, Tbk - Depo Makassar. Utilizing a quantitative research design with a sample of 130 consumers, path analysis using Smart PLS software was conducted to examine the direct and indirect effects of influencer authenticity and marketing effectiveness on consumer engagement and trust. The results reveal significant positive relationships between influencer authenticity and both consumer engagement and trust, highlighting the importance of genuine influencer engagements in fostering consumer connections and confidence in brands. However, while marketing effectiveness positively influences consumer engagement, its impact on consumer trust is not statistically mediated by engagement. These findings underscore the necessity for Unilever to prioritize authentic influencer partnerships and refine marketing strategies tailored to the unique characteristics of the Makassar market to enhance consumer trust and drive long-term brand loyalty and success. Keywords : Influencer Authenticity, Marketing Effectiveness, Consumer Engagement, Consumer Trust